The Effect of Health Education through Providing Marmet Massage on the Knowledge of Breastfeeding Mothers in Increasing Breast Milk Production - Meirna Eka Fitriasnani; Fithri Rif’atul Himmah; Erik Irham Lutfi; Mayasari Putri Ardela (STRADA : Jurnal Ilmiah Kesehatan, 2024)
Mother's milk can educate and improve the quality of the nation's young generation. Every baby who is breastfed will have natural immunity against disease because breast milk contains many antibodies, active immune substances that will fight the entry of infections into the baby's body. Inadequate breast milk production causes the baby's needs to not be met and exclusive breastfeeding fails. The aim of this research is to determine the effect of health education through giving marmet massage on the knowledge of breastfeeding mothers to increase breast milk production.  The research design uses a pre-experimental approach with a one group pre test post test design.